University of Limpopo (Medunsa campus) psychology undergraduates’ knowledge, attitudes, behaviour and beliefs regarding HIV and Aids - Maponyane, Egnetia Selina (University of Limpopo (Medunsa Campus), 2014)
The aim of the study is to investigate the HIV and Aids knowledge, attitudes, behaviour and beliefs of University of Limpopo undergraduate students (Medunsa Campus) registered for modules in psychology. South African tertiary institutions have a high rate of HIV infection. Empirical evidence indicates that generally male students have multiple partners during their years at university. Various studies reveal that the use of condoms is relatively low amongst students. This investigation utilized a quasi-experimental survey design as it was deemed an appropriate method with which to answer the research question. The questions used in the survey were underpinned by the Health Belief Model (HBM) and the Protection Motivation Theory (PMT). Several open-ended questions were added to lend a qualitative aspect to the study. Proportionate stratified sampling was used. Using this method a sample of students was randomly allocated in each educational level (first year, second year and third year) according to the true proportional number of students in each level. Quantitative data was analyses using descriptive statistics and an independent t-test to look for differences between the means of the male and female groups. Results underpinned other research in this arena For instance, the majority of participants indicated that they know that using a male condom or female condom can prevent the spread of Aids. This suggests that this percentage would take the positive health related action of using a condom. However, fifty one respondents (35.66%) indicated that they were very likely to believe that they would feel uncomfortable buying condoms and forty five respondents (31%) were likely to believe that they would feel uncomfortable buying condoms. This indicates that knowledge is not a good predictor of a positive health related action. Quantitative and qualitative results suggest that stigmatizations and racism exist in the samples attitudes towards aspect of HIV and Aids. The only significant result between the means of the two groups suggests that males are more likely to indulge in high risk sexual behaviours than females.
Thesis (MSc (Clinical Psychology)) -- University of Limpopo, 2012.
Keywords: HIV; HIV infection